2 Charles Allen, Report of the Commissioners on the Revision of the Statutes 333 (1881) - (:unkn) unknown (My University, 1881)
Fire Arms, § 18. There shall be in each county, where the manufacture of fire-arms is carried on, provers of fire-arms, not more than six in number, appointed by the governor with the advice and consent of the council, who shall prove all musket barrels and pistol barrels which, being sufficiently ground, bored and breeched, are offered to them to be proved. § 19. All musket barrels and pistol barrels manufactured in this commonwealth shall, before they are sold or stocked, be proved by one of the provers with a ball suited to the bore of the barrel and with a charge of powder equal in weight to the ball.
Keywords: MANUFACTURE ONLY